2005
DOI: 10.1177/0047287505276590
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Tourism Advertising Effectiveness

Abstract: This study builds on previous research on the impact of tourism advertising and argues that there are a number of likely routes through which tourism advertising influences destination choice. Data were obtained from a survey that examined the impact of Illinois travel advertising and was conducted during the fall of 2001. The results confirm that there are strong linkages among top-of-mind awareness, ad awareness, requesting travel information, and the likelihood of visiting a destination, and therefore, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 28 publications
4
89
0
2
Order By: Relevance
“…Along with PLS results, the argument quality and peer tourist source of ITAs could significantly increase perceived usefulness, perceived enjoyment, and satisfaction, and could increase ITA adoption, planned/unplanned visit and word-of-mouth intention of the potential tourists. These results could also be consistent with prior studies' findings that the effectiveness of ITAs could be determined by the destination awareness [8] and destination visit [9]. The results of this study successfully capture how the argument quality and peer tourist source of ITAs could induce the potential tourists' perceptions, attitudes and behavioral intentions toward the ITA.…”
Section: Discussionsupporting
confidence: 88%
“…Along with PLS results, the argument quality and peer tourist source of ITAs could significantly increase perceived usefulness, perceived enjoyment, and satisfaction, and could increase ITA adoption, planned/unplanned visit and word-of-mouth intention of the potential tourists. These results could also be consistent with prior studies' findings that the effectiveness of ITAs could be determined by the destination awareness [8] and destination visit [9]. The results of this study successfully capture how the argument quality and peer tourist source of ITAs could induce the potential tourists' perceptions, attitudes and behavioral intentions toward the ITA.…”
Section: Discussionsupporting
confidence: 88%
“…Kim, Hwang and Fesenmaier (2005) proposed an expanded framework to tourism advertising effectiveness. This study suggested the importance of considering psychological states such as cognitive and behavioural processes, which indicate the sequential advertising response process.…”
Section: Tourism Advertising Effectivenessmentioning
confidence: 99%
“…Tourism advertising is regarded as one of the most influential information sources for prospective and current visitors (Burke & Gitelson, 1990;Kim, Hwang, & Fesenmaier, 2005;Gretzel, Yuan, & Fesenmaier, 2000;USTA, 2011). Recently, many tourism destination organizations (DMOs) in the United States and elsewhere have been challenged by state budget cuts which have led to strong pressure to defend funding for destination-specific tourism advertising (Papatheodorou, Rossello, & Xio, 2010;Ritchie, Molinar, & Frechtling, 2010;Spring, 2010;USTA, 2011).…”
Section: Introductionmentioning
confidence: 99%